A band-gap-graded CZTSSe solar cell with 12.3% efficiency. Issue 26 (20th May 2016) - Yang, Kee-Jeong; Son, Dae-Ho; Sung, Shi-Joon; Sim, Jun-Hyoung; Kim, Young-Ill; Park, Si-Nae; Jeon, Dong-Hwan; Kim, JungSik; Hwang, Dae-Kue; Jeon, Chan-Wook; Nam, Dahyun; Cheong, Hyeonsik; et al.
Abstract : Using an appropriate SeS2 /Se weight ratio, band gap grading was realized. By increasing the value of V OC through band gap grading in the depletion region, a record V OC deficit of 0.576 V and an efficiency of 12.3% were obtained. Abstract : Although Cu2 ZnSn(S, Se)4 (CZTSSe) has attracted attention as an alternative to CuInGaSe2 (CIGS) as an absorber material in solar cells, its low efficiency is a serious shortcoming preventing its commercialization. To realize a high-efficiency CZTSSe solar cell, improved grain crystallinity, inhibited secondary-phase formation, controlled defect generation, adequate Na content, and band gap grading are required in the absorber layer. Few studies have focused specifically on band gap grading. In this study, a method of using SeS2, a new potential chalcogenization source material, to control the S and Se contents in a CZTSSe absorber and its effects were investigated. Using an appropriate SeS2 /Se weight ratio, band gap grading was realized within the depletion region. By increasing the value of V OC through band gap grading in the depletion region, a record V OC deficit of 0.576 V was achieved. Furthermore, the possibility of enhancing J SC through the formation of a type-inverted n-type phase at the absorber surface in response to an appropriate alignment of the conduction-band minimum energy level and the Fermi energy pinning level is discussed. By introducing the chalcogenization source material SeS2 during the annealing process, CZTSSe solar cells with a maximum efficiency of 12.3% were obtained.